Car Service Services Information System and Website-Based Sparepart Sales in the Company PT. Azka Gilang Mandiri - Ritzkal; Willy Mandela; Alief Juan Aprian; Moh Subchan; Moh Risnandar; Hersanto Fajri; Bayu Adhi Prakosa (Jurnal Mantik, 2022)
The development of the website today is not a difficult thing for students and students to learn because there are many references on the internet to support learning. The formulation of the problem in this study is 1. How to automatically set up service and spare parts data on invoices?. 2) How to manage good service and spare parts data management?. The purposes of this research are: 1. Manage the inventory of spare parts data stock, service income, and manage all reports and transactions at the company. 2. Facilitate the administration of the company in the process of providing services and data collection of spare parts, because the website has been managed properly and the company is more organized for use in data collection services and spare parts data. The research method used in this study using Waterfall. The waterfall method is one of the SDLC models that is often used in the development of information systems or software. The waterfall model uses a systematic and sequential approach. The stages of the waterfall model include requirements, design, implementation, verification, and maintenance. Based on the results and discussion, the following conclusions can be drawn: (i) Information systems for services and sales of spare parts can be used as an answer to problems that occur in the management of the workshop, with this system the management of the workshop can be more easily carried out and much faster and the quality of information is more manageable. well. (ii) Development of an information system website for services and spare parts sales for customers of PT. Azka Gilang Mandiri has been carried out and implemented from the results of the designs that have been made in Context Diagrams, System Actors (List Actors), Use Case Diagrams, Activity Diagrams, and Class Diagrams.